RECLINICAL AND LABORATORY FEATURES OF HEMOSTASIS DISORDERS IN PATIENTS WITH RHEUMATOID ARTHRITIS (World Bulletin of Public Health, 2024)
This article discusses the importance of laboratory diagnosis of rheumatoid arthritis as a crucial part of evaluating patients suspected of having this condition. The main methods of laboratory testing, their role in disease diagnosis and monitoring, as well as the interpretation of test results in conjunction with the clinical presentation are analyzed in the article. Key biomarkers are considered, and the peculiarities of laboratory diagnosis in the context of rheumatoid arthritis are discussed. Recommendations for specialists on conducting and evaluating laboratory analyses are provided. The aim of the article is to increase awareness among healthcare providers and patients about the significance of laboratory diagnosis for accurate diagnosis and optimal management of rheumatoid arthritis.